Multinuclear MRS at 7T Uncovers Exercise Driven Differences in Skeletal Muscle Energy Metabolism Between Young and Seniors - Krumpolec, Patrik; Klepochová, Radka; Just, Ivica; Tušek Jelenc, Marjeta; Frollo, Ivan; Ukropec, Jozef; Ukropcová, Barbara; Trattnig, Siegfried; Krššák, Martin; Valkovič, Ladislav (Frontiers in Physiology, 2020)
Purpose: Aging is associated with changes in muscle energy metabolism. Proton (1H) and phosphorous (31P) magnetic resonance spectroscopy (MRS) has been successfully applied for non-invasive investigation of skeletal muscle metabolism. The aim of this study was to detect differences in adenosine triphosphate (ATP) production in the aging muscle by 31P-MRS and to identify potential changes associated with buffer capacity of muscle carnosine by 1H-MRS. Methods: Fifteen young and nineteen elderly volunteers were examined. 1H and 31P-MRS spectra were acquired at high field (7T). The investigation included carnosine quantification using 1H-MRS and resting and dynamic 31P-MRS, both including saturation transfer measurements of phosphocreatine (PCr), and inorganic phosphate (Pi)-to-ATP metabolic fluxes. Results: Elderly volunteers had higher time constant of PCr recovery (τPCr) in comparison to the young volunteers. Exercise was connected with significant decrease in PCr-to-ATP flux in both groups. Moreover, PCr-to-ATP flux was significantly higher in young compared to elderly both at rest and during exercise. Similarly, an increment of Pi-to-ATP flux with exercise was found in both groups but the intergroup difference was only observed during exercise. Elderly had lower muscle carnosine concentration and lower postexercise pH. A strong increase in phosphomonoester (PME) concentration was observed with exercise in elderly, and a faster Pi:PCr kinetics was found in young volunteers compared to elderly during the recovery period. Conclusion: Observations of a massive increment of PME concentration together with high Pi-to-ATP flux during exercise in seniors refer to decreased ability of the muscle to meet the metabolic requirements of exercise and thus a limited ability of seniors to effectively support the exercise load.